The Role of the Wanar Village Consultation Body in Carrying Out Their Tasks and Functions from Fiqh Siyasah Perspective - Wijaya, Arif; Junaidy, Abdul Basith; Syafaq, Hammis; Kurniawan, Cecep Soleh (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
This article discusses the role of the Village Consultative Body in carrying out its duties and functions in Wanar village, Pucuk District, Lamongan Regency, East Java from the perspective of fiqh siyasa. This research is field and qualitative research. Data were collected through observation, interviews and documentation, which was then analyzed deductively. The results of this study concluded that the function and role of the Village Consultative Body of Wanar Village, Pucuk District, Lamongan Regency, had been carried out well. 2 factors affect the performance of BPD Wanar, namely: supporting and blocking factors. The supporting factor is the support from the village community and the village government is a good partner with BPD. The inhibiting factors are the salary of BPD members is still minimal, facilities and infrastructure are inadequate, funding is lacking, the human resources of BPD members are less qualified, and there is rejection by some communities of decisions/policies made by the village head. From the perspective of fiqh siyasah, the role and function of BPD are equated with ahl al-hall wa al-' aqd and the Hisbah institution. In performing its functions, BPD's performance is by the rules of